Emerging roles of bacteriophage-based therapeutics in combating antibiotic resistance - Subramanian, Anandhalakshmi (Frontiers in Microbiology, 2024)
Amid the growing challenge of antibiotic-resistance posing a global challenge, there's been a notable resurgence in bacteriophage-based treatments, signaling a shift in how we approach infections. Bacteriophages BPs, nature's bacterial predators, present a promising alternative for tackling infections caused by antibiotic-resistant pathogens. This review delves into the intricate relationship between bacteriophages and resistant bacteria, exploring various treatment strategies.Drawing upon both preclinical and clinical studies, the review underscores the effectiveness of bacteriophage therapy, particularly when integrated synergistically with conventional antibiotics.It discusses different treatment approaches for both systemic and localized infections, demonstrating the adaptability of bacteriophage therapy across different clinical scenarios.Furthermore, the formulation and delivery of bacteriophages, shed light on the various methods used to encapsulate and administer them effectively. It also acknowledges the challenge of bacterial resistance to bacteriophages and the ongoing efforts to overcome this hurdle.In addition, the review highlights the importance of the bacteriophage sensitivity profile (phagogram), which helps tailor treatment regimens to individual patients and specific pathogens.By surpassing the limitations of traditional antibiotics, bacteriophage-based therapies offer a personalized and potent solution against antibiotic-resistance, promising to reshape the future of infectious disease management.